第43次南極地域観測隊「タンガロア」海洋観測報告(海洋物理) - 青木, 茂; アオキ, シゲル; 佐藤, 壽彦; サトウ, トシヒコ; Aoki, Shigeru; Sato, Toshihiko (2004)
P(論文) 南大洋季節海氷域における生物・化学物質循環過程の解明を中心課題として,第43次日本南極地域観測隊「専用観測船」観測が,2002年2月に観測船「タンガロア」号によって実施された.本報告では海洋物理観測の実施状況および測器の運用結果について報告する.CTD電気伝導度に対する航海前後でのキャリブレーションはドリフトの小さいことを示し,塩分換算での差も平均で0.0014に収まった.XCTDの精度を検証する試みも2キャスト実施され,XCTDとCTDとの比較結果についても議論する.本航海では,概ね,良好な精度の物理観測が実施されたものと結論される. To understand the seasonal variation of biological and biogeochemical cycles in the seasonal ice zone in the Southern Ocean, the cruise of JARE-STAGE (Japanese Antarctic Research Expedition-Studies on Antarctic Ocean and Global Environment) was conducted in February 2002 with R/V Tangaroa. Physical oceanography implementations of the cruise are described. The results of the manufacturers' CTD conductivity calibrations were consistent between before and after the cruise, and the difference in salinity estimate was expected to be within 0.0014. Two casts were made to validate the XCTD accuracy and comparisons with the CTD are discussed. Generally, it is concluded that reasonably accurate observations were completed in this cruise. departmental bulletin paper